(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article presents a comprehensive project of a disinfection device specifically designed to neutralize microorganisms that accumulate on the surface of paper money used in automated teller machines (ATMs). The accumulation of bacteria, viruses, and other harmful pathogens on currency notes poses a significant health risk, especially given the frequent handling by numerous users. To address this issue, the proposed device employs advanced ultraviolet-C (UV-C) radiation technology, which is well known for its germicidal properties. UV-C light effectively inactivates bacteria and viruses by disrupting their DNA and RNA structures, thereby preventing their reproduction and spread. Beyond the core disinfection function, the device is engineered with additional features to enhance the internal environment of the ATM. It incorporates an air filtration system that continuously cleans the air inside the ATM casing, removing dust, airborne microorganisms, and other pollutants. Furthermore, the device maintains a stable temperature within the ATM to ensure optimal operation of both the disinfection system and the ATM’s internal components. The technical design integrates a range of modern electronic components to enable precise control and monitoring. At the heart of the system lies an Arduino control module, which orchestrates the device’s operations based on input from various sensors. The DHT22 sensor monitors temperature and humidity levels inside the ATM to ensure the environment stays within predefined parameters. An OLED display provides real-time visual feedback on the device status, allowing operators or maintenance personnel to easily check system performance. The UV LED lights serve as the primary disinfection source, delivering the required UV-C radiation doses. An air ventilation fan ensures proper airflow to maximize the efficiency of both air filtration and UV exposure.